3-D position analysis of an object using a monocular USB port camera through Java - Dong Youp Lee; Chang Ho Ji; Hee Kwon Ha; Seung Gweon Jeong; Joong Eup Keh; Keun Kug Choi; Chung Duk Kim; Man Hyung Lee (2001 IEEE International Symposium on Industrial Electronics Proceedings, 2001)
This paper's purpose is to obtain 3-D information by using a monocular camera. This system embodies to obtain the height of an object by using a trigonometry method between a reference point of circumstance and an object. It is possible to build up a system regardless of operating system, and then set it up. A USB port camera is used everywhere without a capture board. The Internet can be used by using applet and JMF. The authors regard the camera as fixed and they have developed a real-time JPEG/RTP network camera system using UDP/IP on Ethernet.